Comparative Study of Data Analysis Techniques for Photo-Fenton Degradation of Landfill Leachate - Napoleão, Diovana Aparecida dos Santos; Izário Filho, Hélcio José; Siqueira, Adriano Francisco; Bredda, Eduardo Henrique [UNESP]; de Aguiar, Leandro Gonçalves; Da Rós, Patrícia Caroline Molgero; de Alcântara, Marco Aurélio Kondracki (American Chemical Society (ACS), 2022)
This study applied three different techniques to analyze the photo-Fenton degradation of total organic carbon (initial TOC = 3514.6 mg L-1) in leachate collected from a municipal landfill in Cachoeira Paulista, SP, Brazil. The first technique was design of experiments (DoE), which was used to optimize and assess the influence of process variables on TOC reduction. The second technique involved the use of kinetic equations to describe leachate degradation. The third method consisted in the use of an empirical model for assessing the influence of process variables and optimizing the reaction. Optimization by DoE resulted in a mean TOC reduction of 74.64% after 60 min of reaction, with a 95% confidence interval (CI) of 70.8-76.1%. The kinetic model satisfactorily described the initial phase (10 min) of leachate degradation. The empirical model proved useful to predict the degradation process and allowed identifying the experimental conditions to achieve a mean TOC reduction of 82.7% with a 95% CI of 77.4-88.0%.